Civil Law Liability Regarding Asset Transfers for Tax Evasion Purposes - Sidabutar, Theresa; Tri Sulistiyono; Ratih Damayanti (Indonesian Journal of Law, 2026)
The transfer of assets by taxpayers to avoid tax obligations is a practice that has the potential to harm the state. Although it is often carried out in ways that appear formally lawful, such actions can be categorized as an abuse of law when conducted in bad faith. This study aims to examine the forms of civil legal liability arising from asset transfers undertaken to evade taxes. The research employs a normative juridical method with statutory, conceptual, and case approaches. The data used consist of primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that asset transfers motivated by tax avoidance can give rise to civil liability through mechanisms of unlawful acts based on Article 1365 of the Indonesian Civil Code, as well as through actio pauliana as regulated under Article 1341 of the Indonesian Civil Code. The state, as a tax creditor, has legal standing to file claims for the annulment of transactions that harm state tax revenues. Therefore, synergy between tax law and civil law is necessary to ensure effective law enforcement against tax avoidance practices conducted through asset transfers.